The Effects of Environmental Performance, Inflation and Sales Growth on the Profitability of Basic Industrial and Chemical Companies - Alkadrie, Rajeb; Khairunnisa, Khairunnisa (Economic and Business Horizon, 2023)
This research was conducted to determine the relationship between environmental performance, inflation, and sales growth to the profitability of basic and chemical industry companies listed on the Indonesia Stock Exchange in 2015-2020. Environmental performance is measured by PROPER ratings, inflation is measured by the Consumer Price Index and sales growth is measured by the ratio of sales growth and profitability is measured by Return on Asset (ROA). This research is based on a quantitative method approach. The number of samples obtained was 20 companies using the sample selection method, namely purposive sampling. The type of data used is secondary data obtained from the Indonesia Stock Exchange and other sources. The data of this study were analyzed using panel data regression analysis with a random effect model approach. The results showed that environmental performance has a significant effect on profitability, while inflation and sales growth have an insignificant effect on profitability.